Catalyst-free photocyclization for the synthesis of spiro-fused aromatic organic semiconductor based on SFX. Issue 16 (19th April 2018) - Sun, Ming-Li; Zhang, Feng; Qian, Yan; Ou, Chang-Jin; Liu, Bin; Xie, Ling-Hai; Wei, Ying; Ren, Bao-Yi; Huang, Wei
Abstract: A green protocol with catalyst-free photo-induced cyclization for the synthesis of a spiro-fused organic semiconductor molecule based on spiro[fluorene-9, 9′-xanthene] (SFX) was developed. The photophysical and electrochemical properties of the spiro-fused compound (DPCzSFX) have been characterized. The results showed that the molecular stability and the property of the charge injecting/transporting were improved due to the cyclization. And the broadening of the emission spectrum in film makes the sipro-fused compound possible for the application as a host in the white phosphorescent organic light-emitting diodes. However, the same reaction for the spirobifluorene-based dipenylamine derivative did not occur under the same condition, which also highlights the importance of the oxygen heteroatom in the ring to the reaction of cyclization. Graphical abstract: Image 1